2011
DOI: 10.4038/tar.v22i3.3697
|View full text |Cite
|
Sign up to set email alerts
|

Consumption, Solid Waste Generation and Water Pollution in Pinga Oya Catchment area

Abstract: This study focuses on the effects of socioeconomic and political factors in solid waste generation and water pollution in the catchments of Pinga Oya, a tributary of the Mahaweli river. The direct solid waste disposal into water bodies and the untreated dumping sites are supposed to be some of the major causes of water pollution in Sri Lanka. The main objectives of this paper were to determine and evaluate the causal link between consumption pattern and solid waste generation and to understand the underlining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 2 publications
0
18
0
Order By: Relevance
“…This cannot reveal the influence of different consumption patterns on MSW generation. It is proposed that residents’ consumption level and consumption patterns will not only affect the MSW volumes, but also affect the composition of MSW [19]. Therefore, to accurately depict the features of MSW generation and develop appropriate MSW management strategies, it is important to consider the impact mechanism of residents’ consumption behavior on MSW generation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This cannot reveal the influence of different consumption patterns on MSW generation. It is proposed that residents’ consumption level and consumption patterns will not only affect the MSW volumes, but also affect the composition of MSW [19]. Therefore, to accurately depict the features of MSW generation and develop appropriate MSW management strategies, it is important to consider the impact mechanism of residents’ consumption behavior on MSW generation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some authors analyzed the impact of consumption factors on the generation of municipal solid waste (Liu et al (2019); Lu et al (2017); Mahees et al 2011;Hage et al 2018). The results showed that developing regions generate more waste than developed regions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…average nearly double that (Asian Institute of Technology, 2004). Having studied the solid waste management patterns in the Pinga Oya environs (Harispattuwa, Akurana, Pujapitiya and Patha Dumabara) in Kandy suburbs, Mahees et al (2011) came out with a linear function to explain per capita solid waste generation (in grammes) in terms of weekly expenditure on food, where every rupee of additional expenditure would be associated with 0.142 grammes of additional solid waste generation. Colombo, the commercial capital and the most urbanized city, is the largest producer of solid waste in Sri Lanka (Bandara, 2008).…”
Section: Waste Generation and Determinantsmentioning
confidence: 99%